Bio-inspired synthesis of metal nanomaterials and applications - Huang, Jiale; Lin, Liqin; Sun, Daohua; Chen, Huimei; Yang, Dapeng; Li, Qingbiao (Chemical Society reviews, 2015)
This critical review focuses on recent advances in the bio-inspired synthesis of metal nanomaterials (MNMs) using microorganisms, viruses, plants, proteins and DNA molecules as well as their applications in various fields. Prospects in the design of bio-inspired MNMs for novel applications are also discussed.